The role of phytomelatonin receptor 1-mediated signaling in plant growth and stress response - Khan, Dawood; Cai, Nan; Zhu, Weilin; Li, Leilin; Guan, Miao; Pu, Xiaojun; Chen, Qi (Frontiers in Plant Science, 2023)
Phytomelatonin is a pleiotropic molecule that ubiquitously presents in plants and acts as a growth regulator and/or signaling molecule regulating plant growth, development and stress responses. Unlike biosynthesis in mammals, phytomelatonin is synthesized from tryptophan in multiple plant’s subcellular compartmentations and is produced in consecutive steps catalyzed by tryptophan decarboxylase (TDC), serotonin hydroxylase (T5H), serotonin acyltransferase (SNAT), and caffeic acid-3-O-methyltransferase (ASMT) and/or caffeic acid-3-O-methyltransferase (COMT), suggesting that subcellular distribution and control of phytomelatonin in a specific compartmentation manner may exist in plant cells. The recent identification of phytomelatonin receptor PMTR1 in several plant species is a turning point in this research field, making the phytomelatonin-dependent signals transited from an all-or-nothing strategy to a PMTR1-modulated strategy in which phytomelatonin signaling could be regulated in a PMTR1-dependent manner. Here we summarize recent evidence in our understanding of PMTR1-mediated regulatory pathways that link melatonin sensing and signaling of external environmental stimuli. We also emphasize that while not all of PMTR1-mediated phytomelatonin signals via G-protein signaling and plant’s responses to stresses regulated by phytomelatonin are largely PMTR1-dependent. Based on the structural comparison of mammal’s melatonin receptor (MT1) and PMTR1 homologues, we propose that similarity in three-dimensional structure of phytomelatonin receptors probably represents a convergent evolution of melatonin recognition in different species.